Managing Corporate Distress in the Philippines : Some Policy Recommendations - Woodruff, Charles (IMF Working Papers; Working Paper, 1998)
While not widespread, the Philippine corporate sector is showing some signs of stress. The paper reviews the exposure of banks to distressed corporate borrowers, the ownership structure of the corporate sector, including the interlocking relationship of corporations and banks, and the legal framework in place for the resolution of debts of distressed companies and the protection of creditor rights. It recommends that immediate measures be taken to improve transparency and regulatory oversight, and to quickly resolve the debts of distressed companies by strengthening the policy framework and institutional capacity for suspension of debt payments by the Securities and Exchange Commission.